1998
DOI: 10.1007/pl00006389
|View full text |Cite
|
Sign up to set email alerts
|

Conflict Among Individual Mitochondrial Proteins in Resolving the Phylogeny of Eutherian Orders

Abstract: The phylogenetic relationship among primates, ferungulates (artiodactyls + cetaceans + perissodactyls + carnivores), and rodents was examined using proteins encoded by the H strand of mtDNA, with marsupials and monotremes as the outgroup. Trees estimated from individual proteins were compared in detail with the tree estimated from all 12 proteins (either concatenated or summing up log-likelihood scores for each gene). Although the overall evidence strongly suggests ((primates, ferungulates), rodents), the ND1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
123
4
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 220 publications
(148 citation statements)
references
References 69 publications
20
123
4
1
Order By: Relevance
“…,(L, C)), A), S). The second data set (lower half) has a total of 1,209 amino acid positions (131 aa more), but the number of different site patterns is 792 (14) or 770 (13) for either 14 or 13 sequences (without Neoceratodus), respectively. The proportionally higher number of site patterns indicates that the additional portion of the amino acid sequences is more variable.The topologies tested are the same as in the first data set.…”
Section: Rag1 Data Setmentioning
confidence: 99%
See 2 more Smart Citations
“…,(L, C)), A), S). The second data set (lower half) has a total of 1,209 amino acid positions (131 aa more), but the number of different site patterns is 792 (14) or 770 (13) for either 14 or 13 sequences (without Neoceratodus), respectively. The proportionally higher number of site patterns indicates that the additional portion of the amino acid sequences is more variable.The topologies tested are the same as in the first data set.…”
Section: Rag1 Data Setmentioning
confidence: 99%
“…The most recent paleontological evidence demonstrated that the lungfish represent an ancient lineage and that several of the features defining this group remained highly conserved throughout the entire evolutionary history of land vertebrates (10). The majority of palaeontological studies published during the last decade suggest that lungfish (Dipnoi) are the closest living relatives of the tetrapods or, alternatively, that coelacanths and lungfish form a monophyletic group that is equally closely related to the land vertebrates (11,12).A wealth of molecular phylogenetic studies addressed the tetrapod origin question, first based on mitochondrial DNA data by using partial gene sequences, single genes, or a few genes, and more recently, based on complete mitochondrial genomes (9,(13)(14)(15)(16)(17)(18). Most of these mitochondria-based molecular phylogenetic studies favored the lungfish as the closest living relatives of tetrapods.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We inferred the phylogenetic relationships using the ABPR algorithm for: (a) a short fragment of 898 bp from the mitochondrial genome of 12 species of primates (Hayasaka et al, 1988); (b) 1757 bp for 19 almostcomplete mitochondrial genomes of birds (Pereira and Baker, 2006); (c) 18,748 bp for 20 complete mitochondrial genomes of mammals (Cao et al, 1998;Perretto and Lopes, 2005); and (d) 16,608 bp from 186 human mitochondrial genomes (Ingman and Gyllensten, 2006). The phylogenetic relationships among the sequences included in these data sets are relatively well known, which facilitates the evaluation of the APBR algorithm in recovering "known" phylogenetic trees.…”
Section: Empirical Data Setsmentioning
confidence: 99%
“…There are a number of such fixed rate matrices that have rates based on the analysis of inferred amino acid changes from various databases. These models include the Jones (Jones et al 1992), Dayhoff (Dayhoff et al 1978), Mtrev (Adachi & Hasegawa 1996), WAG (Whelan & Goldman 2001), Mtmam (Cao et al 1998;Yang et al 1998), Rtrev (Dimmic et al 2002), Cprev (Adachi et al 2000), Blosum (Henikoff & Henikoff 1992), ECM (Empirical Codon Model; Kosiol et al 2007) and Vt (Muller & Vingron 2000). The Poisson model, which is isomorphic to the Jukes & Cantor (1969) nucleotide substitution model, can also be considered a member of the family of fixed amino acid models (Bishop & Friday 1987).…”
Section: Introductionmentioning
confidence: 99%